NUTRITION ASSISTANCE INCREASES THE SIZE OF MIDDLE-UPPER ARM CIRCUMFERENCE OF PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY - Abadi, Ellyani; Putri, Linda Ayu Rizka (YCAB Publisher & IAKMI SULTRA, 2020)
Background: Chronic Energy Deficiency (CED) in pregnant women is characterized by the size of middle-upper arm circumference (MUAC) <23.5 cm. In 2017, the prevalence of CED in Indonesia was 17.3%, 21.9%, 14.37%, and 11.04%, respectively, in Southeast Sulawesi, Kendari, and Puuwatu Health Center, which were still above the national target of 5%. Thus, there is a need to overcome the CED problems by administering nutrition assistance to pregnant women.Objective: This research aimed to understand the effect of nutrition assistance on the size of the middle-upper circumference of pregnant women with CED in the working area of Puuwatu Health Center, Kendari, Indonesia.Methods: This study was a pre-experimental study with one group pretest-posttest design conducted from June to August 2020 in the working area of Puuwatu Health Center. As many as 35 pregnant women with CED living in the work area of Puuwatu Health Center during a period of January-August were enrolled in the study through a purposive sampling method. Later, the data were analyzed using a Wilcoxon sign rank test.Results: There was an effect of nutrition assistance to the size of the middle-upper arm circumference of pregnant women with CED with a p-value= 0.000.Conclusion: The nutrition assistance increases the size of the middle-upper arm circumference of pregnant women with CED in the working area of Puuwatu Health Center.